Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • Strategic Planning in Public Secondary Schools in the Southern Governorates of Palestine and its Relationship to Competitive Advantage Mr. Bahaa Darwish Alghirbawi,Ms. Zenat Hamed Kuhail, Prof. Sleman Hussein Al-Mozeyn • Obstacles to developing cognitive creativity among secondary school students in Al-Baha region from the perspective of their teachers and ways to address them in light of Vision 2030 and contemporary global trends Mr. Ibrahim Mubarak Ahmed Al-Zahrani • The Relationship between Teachers’ Spatial Job Stability and Job Performance: An Analytical Field Study in Muscat Governorate Schools in the Sultanate of Oman Dt. Mohammed Suleiman Al-Baluoshi • Perceptions of Self-Evaluation Team Members Regarding Implementation Challenges: A Qualitative Study Based on the Experience of Self-Evaluation in Primary Schools in Southern Khamis Mushait Ms. Sarah Ajlan Al-Shahri • Talent Management: From Emergence to Development (A Conceptual Study of the Term and Its Dimensions) Mr. Sami Hamed Almalki • Emotional Exhaustion and Its Relationship with Professional Performance Among Faculty Members of the College of Education at the University of Hail Ms. Rehab Mujzi Al-Shammari ,Ms. Malkah Murdi Al-Mutawea ,Ms. Bashayr Nawaf Assaf Al-Shammari • Self-compassion and its relationship to psychological well-being among female students at the University of Hail Ms. Rehab Mujzi Alshammari • Interventions to Promote Executive Development in Children and Adolescents Ms. Elmoujahid Oumaima